Relationship of Interests Following HP Technician Training with Learning Outcomes at the Multy Flash Course and Training Institute in Payakumbuh City - Nindi Putri Dinanti; Jalius Jalius (Universitas Negeri Padang, 2021)
This research was motivated by the high learning outcomes of HP technician training participants at the Payakumbuh Multy Flash Training and Training Institute. The high learning outcomes are thought to be caused by the high interest of the participants in the training. This study aims to: 1) describe the participants' interest in participating in the training; 2) Describe the learning outcomes of participants; and 3) looking at the relationship between interest in training with the learning outcomes of HP technician training participants at the Payakumbuh Multy Flash Training and Training Institute. This type of research is quantitative research with correlational descriptive techniques. The population of this study was all training participants, totaling 30 participants for the period December 2019-March 2020 with a sample taken of 66%, namely 20 people. Samples were taken using simple random sampling technique. The data collection technique is in the form of a questionnaire with the data collection tool in the form of a questionnaire. The data analysis technique used the percentage formula and Spearman rho correlation. The results showed that: (1) the participants' interest in participating in the training was high; 2) the learning outcomes of the participants looked very good; and 3) there is a significant relationship between the Interest in Following HP Technician Training with Learning Outcomes at the Payakumbuh Multy Flash Training and Training Institute. It is recommended that instructors be able to improve their professional skills in order to foster participants' interest in participating in training and for further researchers to look at other variables related to learning outcomes.Keywords: Interests, Learning Outcomes, Training